A DIALOGUE BETWEEN DALITS AND BIBLE: Certain Indicators for Interpretation - Raja, A Maria Arul (Journal of Dharma, 1999)
Ramanathapuram of Tamilnadu state in south India has recently witnessed yet another event of the series of unabated atrocities against Dalits in October 1998. The phenomenon of increasing atrocities unleashed against the .Dalits by the anti-Dalit caste groups is "attributable to the stratified caste structure having under strain because of the increasing assertiveness of the traditionally oppressed sections - the growing tendency of the political class to play upon the caste equations for partisan ends has inevitably resulted in the sharpeningof the caste divide.